Development of Web-Based Learning Media for Junior High School Level Physics Olympiad Material With Islamic Integration - Nani Sunarmi (Jurnal Inovasi Pendidikan dan Sains, 2024)
The Development of Islamic Integrated Learning Website-Based Media for Junior High School Physics Olympiad Material aims to determine the feasibility of the website-based learning media for junior high school physics Olympiad material integrated with Islam. The learning media is developed based on the stages in this research, adopting modifications from Borg & Gall. The data collection instrument used in this research and development is a questionnaire. The results of the development of the junior high school physics Olympiad material website integrated with Islam meet the validity criteria. The average total score of the website media expert is 89.2, the material expert's website validation is 86.15, and the integration of Islamic website validation is 81.82. Considering the overall aspects of validation and meeting the feasibility criteria, it is declared in the "valid/appropriate" category.